Islam And Cultural Locality Of Nyekar Tradition In Indonesia - yunita, iin; Kusumaningrum, Sri Anisa Dewi; Setya Putri, Lovena Tamaya; Lailatusubha, Nur; Hakim Lac, Muhammad Lukman; Noor, Aditia Muhammad (Universitas Nahdlatul Ulama Sunan Giri, 2023)
Nyekar or commonly known as cemetery pilgrimage is a culture in Indonesia that is frequently carried out by the Javanese community. It involves scattering flowers on graves and praying collectively. Nyekar is done to remind people of the inevitability of death that will eventually befall all living creatures in the world. This research focuses on the history of the tradition of pilgrimage or nyekar in Indonesia, the tradition of nyekar itself from an Islamic perspective, and the purpose of the pilgrimage tradition in various regions of Indonesia. The aim of this research is to understand the history of the emergence of the pilgrimage tradition in Indonesia, to understand pilgrimage according to Islamic views, and to understand the purpose of pilgrimage in several regions in Indonesia. This research uses secondary data such as journals, articles, and other relevant sources. The study was conducted by collecting data from written sources related to the research topic. However, some of the main issues in this research are still based on empirical answers found in the study. The results of this research indicate that the nyekar tradition was formed due to the cultural acculturation of Islam, Javanese, and Hindu traditions. In the Islamic view, cemetery pilgrimage or nyekar was initially forbidden as a form of worship but later encouraged in religion. The purpose and goals of cemetery pilgrimage differ from each individual, depending on their beliefs and intentions.